2008
DOI: 10.17221/310-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of changes in selected parameters in relation to different air temperature in the farrowing house for sows

Abstract: ABSTRACT:The purpose of this study was to analyse the influence of different external air temperature on changes in the air temperature of housing environment in the farrowing house for sows and consequent changes in selected parameters of performance in purebred Landrace sows and gilts. Raw data were analysed for 236 litters. The litters were born from October 2004 to March 2006. Air temperature in the farrowing house was monitored in the sow's living zone and was closely related to changes in external air te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…This is in agreement with the observations of Odehnalova et al (2008) who reported that the lowest number of stillborn piglets were seen in deliveries at optimal room temperature (16-22ºC). Machado-Neto et al (1987) demonstrated that elevated temperature around farrowing exerted stress on the sow, resulting in a higher cortisol concentration in the blood serum.…”
Section: Stress/farrowing Environmentsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the observations of Odehnalova et al (2008) who reported that the lowest number of stillborn piglets were seen in deliveries at optimal room temperature (16-22ºC). Machado-Neto et al (1987) demonstrated that elevated temperature around farrowing exerted stress on the sow, resulting in a higher cortisol concentration in the blood serum.…”
Section: Stress/farrowing Environmentsupporting
confidence: 93%
“…However, data on the impact of managemental related factors on stillborn piglets are scarce and mainly focused on supervision of farrowing (Holyoake et al, 1995;Le Cozler et al, 2002;Lucia et al, 2002), pen design (Fraser et al, 1997), ambient temperature (Odehnalova et al, 2008) or dietary fibre (Guillemet et al, 2007).…”
Section: Stress/farrowing Environmentmentioning
confidence: 99%
“…Numerous predisposing factors are incriminated in this situation; some are directly related to sows while others are attributed to the piglets themselves (van Dijk et al 2005(van Dijk et al , 2006Alonso-Spilsbury et al 2007). The most important maternal factors involved in neonatal viability are number of parturitions, mothering skills, diameter of the pelvic canal, abnormal hormonal regulation and uterine physiology, prolonged expulsion periods secondary uterine inertia (uterine atony), maternal hypoxia resulting from temperatures above 35 °C in the delivery room, among many others (Alonso-Spilsbury et al 2005, 2007Odehnalova et al 2008;Olmos-Hernandez et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The transitional period during expulsion from the uterus to the birth of a newborn is of utmost importance since many adaptation problems may be detected, such as thermoregulation alterations and breathing difficulties (Odehnalová et al, 2008). The understanding of normal transitional physiological changes of the newborn piglets is important for evaluating their vitality (Sanchez et al, 2009;Maniau et al, 2010).…”
mentioning
confidence: 99%